Should Students Keep on Learning Writing although Facing Problems and Feeling Less Confident? - Shofi Nurmala Sari; Lestari Setyowati (Universitas Sembilanbelas November Kolaka, 2021)
Learning to write in English is not an easy task. Foreign language learners (EFL) need to put their best effort to produce an acceptable piece of writing in terms of content and language. This paper is intended to investigate the English Language Education problems in writing essays. This study uses a descriptive-quantitative design, by using mini-scale research on the 2020 batch of students taking essay writing courses this semester. The total population of the participants is 120 students, Yet, the researchers only took 17% of the total population as the respondents. The instrument used is a five-scale questionnaire in which all items exploring the students’ problems in writing. The researchers distributed the questionnaire randomly to 20 students by using a google form application. The result shows that the problems frequently faced by the students are the writers' block during writing. All students also felt that the lack of reading affects the progress of their writing. Furthermore, the students felt they have problems in using proper grammar and how to make the essay intact. As a result, there are 65% of the students do not have enough confidence in writing, and only 30% of them are sufficiently confident with their writing ability.